Relationship Between Body Mass Index and Low Skeletal Muscle Mass in Adults Based on NHANES 2011–2018 - Rong-Zhen Xie; Xu-Song Li; Fang-Di Zha; Guo-Qing Li; Wei-Qiang Zhao; Yu-Feng Liang; Jie-Feng Huang (Scientific Reports)
Abstract Sarcopenia, a syndrome characterized by declining muscle mass and function, is associated with various adverse health outcomes. While body mass index (BMI) is a fundamental health indicator, its relationship with sarcopenia is complex and remains inadequately explored. Low BMI has been linked to muscle loss, but the role of other demographic and clinical factors in this relationship is unclear. This cross-sectional study analyzed data from the NHANES 2011–2018 cohort, including 7,455 adults aged ≥ 20 years. Low muscle mass was diagnosed based on appendicular skeletal muscle mass using DXA criteria. BMI was categorized into quartiles for analysis. Weighted multivariable logistic regression assessed associations between BMI and low muscle mass, adjusting for confounders such as age, gender, ethnicity, income-to-poverty ratio, and chronic diseases (e.g., diabetes and hypertension). Variance inflation factors (VIF) confirmed the absence of multicollinearity. Lower BMI was significantly associated with higher odds of low muscle mass (adjusted OR: 0.508, 95% CI: 0.483–0.533, p < 0.001), while higher BMI exhibited a protective effect. Age (OR: 1.035, 95% CI: 1.025–1.045, p < 0.001) and female gender (OR: 1.570, 95% CI: 1.267–1.949, p < 0.001) were independent risk factors. Racial disparities were noted, with non-Hispanic Black individuals at lower risk compared to non-Hispanic Whites (OR: 0.242, 95% CI: 0.152–0.384, p < 0.001). Other significant factors included diabetes and alcohol consumption, while education and smoking status were not significantly associated. BMI is inversely associated with low muscle mass prevalence, with lower BMI posing a higher odds. The findings underscore the clinical importance of monitoring BMI and addressing multifactorial risk profiles for low muscle mass management and prevention.